(untitled) (Atti del Sodalizio Glottologico Milanese, 2023)
This paper aims to describe Luigi Heilmann’s structural point of view. A philologist and linguist, a specialist in Indology, Semitistics, and Romance dialectology, he subscribed to the Prague School functional perspective and put his structural method in continuity with the comparative-historical method. Heilmann was open to scientific dialogue, also from an interdisciplinary perspective which he based on two principles: a generative humanitas and an interpretative structure.